Integration of hydrogeophysical and geological investigations in enhancing groundwater potential assessment in Houtriver gneiss crystalline basement formation of South Africa - Muchingami, I.; Mkali, A.; Vinqi, L.; Pietersen, K.; Xu, Y.; Whitehead, R.; Karsten, J.; Villholth, Karen G.; Kanyerere, T. (Elsevier, 2021)
Groundwater exploration in crystalline basement aquifers such as the Houtriver gneiss formation in the Limpopo province of South Africa is often described as complex. This is because groundwater availability in such aquifers is largely a consequence of the interaction of several processes related to recharge, underlying geological features and fracture connectivity of the aquifer rock matrix. In this study, an integration of geophysical and geological investigations is applied in inferring potential drill targets within the Houtriver gneiss crystalline basement aquifer system. Results from the magnetic and frequency domain electromagnetic surveys were combined with geological investigations to identify sites where vertical electrical resistivity sounding was applied to infer the thickness and layering of weathered and fractured zones, as well as to identify potential targets where test boreholes were drilled. Constructed geo-resistivity pseudo-sections suggested that groundwater occurrence within this formation is described by a heterogeneous multiple-layered and fractured aquifer system with the main groundwater bearing zones ranging from a depth of 30–72m in most cases. Ten potential drill sites were identified from which three test boreholes were drilled and used to validate the results through a lithostratigraphic conceptual model developed from the correlation of the geophysical results with drill logs. The integration of hydro-geophysical and geological methods thus provided a comprehensive approach for resource assessment in the Houtriver gneiss formation.